Time Budget Pressure Effect, Auditor Ethics, Audit Fee and Auditor's Working Experiences on Audit Quality - Ida Ayu Budhananda Munidewi; Ni Made Sunarsih (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
Audit quality is the probability of an auditor finding and reporting an error or fraud in a client's accounting system. It is critical to ensure that the accounting profession fulfills its responsibilities to the public in producing reliable and quality audit reports. This study aims to test and obtain empirical evidence, audit ethics, audit fees, and work experience of auditors on audit quality at public accounting firms in Bali. The population in this study were 117 auditors at the Public Accounting Firm in Bali listed in the IAPI Directory in 2020, with a total sample of 67 respondents from 16 Public Accounting Firms obtained by the non- probability sampling method with purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that time budget pressure and auditor ethics affects audit quality, while audit fees and auditor work experience do not affect audit quality. Further research can be developed by adding other variables that can affect audit quality.